2021
DOI: 10.1186/s40468-021-00147-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of test performance on paper-based testing (PBT) and computer-based testing (CBT) by English-majored undergraduate students in China

Abstract: Computer-based testing (CBT), which refers to delivering assessments with computers, has been widely used in large English proficiency tests worldwide. Despite an increasing CBT in China, limited research is available concerning whether CBT can be used for the Test for English Majors-Band 4 (TEM 4). The current study investigated whether testing mode impacted TEM 4 score and factors (i.e., computer familiarity level and attitude towards CBT) that might correlate with performance on CBT of TEM 4. Overall 92 Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
3
8
0
Order By: Relevance
“…Additionally, no significant differences were found in test scores between the participants of the experimental and the controlled groups. Likewise, Yu and Iwashita (2021) randomly assigned 92 Chinese undergraduate students to an experimental group using CBT, and a controlled group using PBT. The test scores were compared, and semi-structured interviews (Pekrun, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, no significant differences were found in test scores between the participants of the experimental and the controlled groups. Likewise, Yu and Iwashita (2021) randomly assigned 92 Chinese undergraduate students to an experimental group using CBT, and a controlled group using PBT. The test scores were compared, and semi-structured interviews (Pekrun, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies such as Öz and Özturan (2018) and Yu and Iwashita (2021) showed that computerbased testing can be integrated into university education without fears regarding test validity, reliability, or scores. However, the area that still needs further exploration is students' acceptance of this mode of testing (Zheng & Bender, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is because students who do tests on screen have a variety of concerns and problems on computer-based examinations, such as noisy keyboards, assessment of spelling, and unfairness rather than those who are less comfortable with the technology (Yeom, Jun, 2020). In addition, research by W. Yu and N. Iwashita (Yu, Iwashita, 2021) indicates that the students' attitude towards MBA does not have a positive impact on their performance. Complementarily, in their research H. Öz and T. Özturan (Öz, Özturan, 2018) show that there is not any significant difference in test scores between the participants who take the computer-based test and those who take the paper-based test.…”
Section: Introductionmentioning
confidence: 99%
“…Test-takers’ perceptions of and preferences for computerized testing are commonly measured aspects of computer familiarity that have drawn much attention in cross-modality studies. According to the literature, an increasing number of test-taker populations at a whole-group level positively perceive or prefer CBW assessment for a range of reasons, including convenience and efficiency of the test and confidence in and adeptness at typing (e.g., Feng et al, 2019 ; Kim et al, 2019 ; Lee, 2004 ; Yu & Iwashita, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A related area that has also been popularly explored in many questionnaire-based studies is the effect of test-takers’ computer familiarity on CBW test scores at a whole-group level; yet, the end result is inconclusive due to mixed findings. Some studies have revealed that the computer usage-related factor positively affects test scores or has interaction effects with computer use experiences on test scores (e.g., Breland et al, 2005 ; Lee, 2004 ; Yu & Iwashita, 2021 ). According to Jin and Yan ( 2017 ), test-takers with high levels of computer familiarity performed better on the computer version of the College English Test (CET) in China.…”
Section: Introductionmentioning
confidence: 99%